Issue Information. Issue 1 (19th September 2020) - Unknown
Abstract : Cover : In Xu et al. (http://doi.org/10.1002/cpcy.78 ), the image shows single‐color imaging of histone modifications in pathological tissue. (A1 ‐B1 ) H&E‐stained pathology images and (A4 ‐B4 ) STORM images of heterochromatin stained with H3K9me3 and H3K27me3 of normal tissue from wild‐type mice. (A2 ‐B2 ) Conventional wide‐field fluorescence images and (A5 ‐B5 ) corresponding STORM images of heterochromatin from a single nucleus. (A3 ‐B3 ) and (A6 ‐B6 ) are progressively zoomed regions of (A2 ‐B2 ) and (A5 ‐B5 ).